NIMG-21. FROM BEYOND THE MARGIN: HIGH ANGULAR RESOLUTION Q-SPACE MRI MAY DETECT GLIOBLASTOMA TUMOR CELL INVASION INTO BRAIN PARENCHYMA. (11th November 2019) - Leary, Owen; Toms, Steven; Zepecki, John; Merck, Derek; Tapinos, Nikos; Gilbert, Richard
Abstract: BACKGROUND: Invasion of glioblastoma tumor cells beyond the visible margins is hypothesized to mediate tumor spread and recurrence, and thereby affect poor survival. Radiomic biomarkers associated with the extent of tumor infiltration are virtually non-existent. METHODS: Seven subjects diagnosed with glioblastoma underwent high resolution "Q-Space" diffusion-weighted MRI sequences (Siemens 3T scanner, 64 gradient directions, b-value=1000s/mm 2 ) during pre-operative MRI workup. For each subject, the largest tumor was manually segmented, and patterns of probabilistic inter-voxel coherence intersecting each segmentation generated as tractograms using DSI Studio (length=0–200mm, AT=30º). Separately, immunodeficient (Nu/J) mice were injected sub-hippocampally with patient-derived glioma stem cells (GSCs) using stereotactic guidance. Two months after injection, mice were sacrificed, resected brains were scanned on a Bruker 7T MRI using cryoprobe with T2-weighted and diffusion-weighted sequences (512 directions), and tumor-intersecting tractography displayed. 3D whole-brain reconstruction of the same xenograft model, stained with anti-human mitochondrial antibody, was performed for comparison. In one patient undergoing resection of fronto-temporal glioblastoma, BrainLab intraoperative navigation was used for stereotactic biopsy of extra-tumor parenchymal samples localized according to proximity to tumor-intersecting tractography. RNA-seq was performed on all samples using Illumina HiSeq2500 by a blinded analyst. RESULTS: All human tumors (n=7) displayed region-specific long projecting tracts extending into brain parenchyma (Mean=23.2mm, SD=3.1mm). Maximum tract length varied from 80–130mm (Mean=102mm, SD=20.4mm). Xenograft models displayed similar tumor-intersecting tractography (n=3), with 3D reconstruction of stained GSCs replicating that pattern. RNAseq data revealed significant overrepresentation (≥2-fold) of 528 transcripts in projecting tumor tract-associated samples compared to samples obtained from the tumor mass itself and brain parenchyma unassociated with projecting tumor tracts. Functional classification revealed that 62% of these transcripts regulate cell motility as part of inter-related networks. CONCLUSION: These imaging data, backed by region-specific transcriptomic evidence, suggest that Q-Space MRI may discriminate localizable patterns of inter-voxel coherence representing tumor-associated infiltration pathways in glioblastoma.